2007
DOI: 10.1021/ja0762994
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Mechanistic Study of AlIII-Catalyzed Transamidation of Tertiary Amides

Abstract: Cleavage of the C-N bond of carboxamides generally requires harsh conditions. This study reveals that tris(amido)Al(III) catalysts, such as Al2(NMe2)6, promote facile equilibrium-controlled transamidation of tertiary carboxamides with secondary amines. The mechanism of these reactions was investigated by kinetic, spectroscopic, and density functional theory (DFT) computational methods. The catalyst resting state consists of an equilibrium mixture of a tris(amido)Al(III) dimer and a monomeric tris(amido)Al(III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 8 publications
0
54
0
Order By: Relevance
“…Stahl demonstrated that a tris(amidate) aluminium species was the resting state of the catalyst in his transamidation chemistry and that catalytically viable species were generated through facile ligand substitution reactions under the reaction conditions. [35,36] We suggest similar fluxionality here, where one of the amidate ligands is protonated off of the aluminium ion by an equivalent of 2-propoanol to generate a catalytically viable Al-alkoxide under the reaction conditions. [52] We also investigated the competency of the Al-amidate complexes to serve as catalysts for the Oppenauer oxidation [53] of alcohols to the corresponding carbonyl compounds.…”
Section: Catalytic Activity Of the Al-amidate Complexesmentioning
confidence: 93%
See 1 more Smart Citation
“…Stahl demonstrated that a tris(amidate) aluminium species was the resting state of the catalyst in his transamidation chemistry and that catalytically viable species were generated through facile ligand substitution reactions under the reaction conditions. [35,36] We suggest similar fluxionality here, where one of the amidate ligands is protonated off of the aluminium ion by an equivalent of 2-propoanol to generate a catalytically viable Al-alkoxide under the reaction conditions. [52] We also investigated the competency of the Al-amidate complexes to serve as catalysts for the Oppenauer oxidation [53] of alcohols to the corresponding carbonyl compounds.…”
Section: Catalytic Activity Of the Al-amidate Complexesmentioning
confidence: 93%
“…[33] Despite these chemistries, the application of aluminium amidate complexes as catalysts has not been investigated. The Stahl group has reported the Al 2 (NMe 2 ) 6 -catalyzed transamidation of carboxamides, [34] and has shown that aluminium amidate functional groups are important moieties under the reaction conditions, [35,36] suggesting that Al-amidate complexes may be viable catalytic species. Herein, we report the synthesis of a series of Al-amidate complexes that vary in ligand : metal stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…101 This method allowed stoichiometric amounts of AlCl 3 to be used to N-acylate primary and secondary amines using activated N-tosyl, N-benzoyl, and Npivaloylamides as acyl donors. Gellman and coworkers have described a series of metal-catalyzed equilibrium-controlled transamidation reactions of primary and secondary amines using secondary and tertiary amides as acyl donors, [102][103][104] with Zr(NMe 2 ) 4 found to be a particularly efficient catalyst for the transamidation of secondary amines using tertiary amides ( Figure 18). 104 Impressively, this catalytic system also promoted tertiary amide metathesis at room temperature, affording transamidation protocols with significant potential for dynamic combinatorial chemistry applications.…”
Section: N-acyl Transfer Reagentsmentioning
confidence: 99%
“…The thermodynamically controlled amide exchange may be catalyzed by amidoaluminum complexes in organic solvents; however, the relatively high temperatures required (90 -120 ° C) represent a limitation for its use in DCLs of receptors [42,43] . Alternatively, enzyme -catalyzed transimination has been reported.…”
Section: Esters and Related Connectionsmentioning
confidence: 99%